The Effect of Circuit Training Method on T Kick Speed of Pencak Silat Athletes - Muhammad Alkhalish; Mulyana; Widi Kusumah (Journal of Physical Education Health and Sport, 2025)
This study aims to determine the effect of circuit training on T-kick speed in pencak silat athletes. The method used is a quasi-experimental with a pretest-posttest control group design. The sample consisted of 20 athletes who were randomly divided into two groups: experimental and control. The experimental group underwent a circuit training program for four weeks, while the control group underwent conventional training. Kick speed measurements were carried out using Kinovea software. The results of the Paired Sample t-Test showed a significance value of 0.000 (p <0.05), which indicated a significant increase in the experimental group. The average T-kick time decreased from 0.76070 seconds to 0.64250 seconds. This study shows that circuit training can significantly increase kick speed by increasing leg muscle strength, neuromuscular efficiency, and motor coordination. These findings contribute to the development of more specific and technology-based training methods in pencak silat.